The alchemy of food : the secrets of the great art of cooking and the healing effects of fine cuisine - Schleicher, Peter; Witzigmann, Eckart , 1941- (Evans Mitchell Books, 2010)
The Alchemy of Food is a cookbook with a difference. Aimed at those suffering from cancer, it traces the origins of alchemy and its illustrious practitioners and draws parallels between the art of alchemy and cooking